2019
DOI: 10.2147/ott.s235195
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brain Metastases Completely Disappear in Non-Small Cell Lung Cancer Using Hydrogen Gas Inhalation: A Case Report</p>

Abstract: Lung cancer is the most common type of tumor, prone to contralateral lung, bone and brain metastasis. We report a 44-year-old woman diagnosed with lung cancer with multiple metastases in November 2015. Oral targeted drugs were initiated after the removal of brain metastases, and most lesions remained stable for 28 months. In March 2018, intracranial multiple metastases, as well as hydrocephalus accumulation in the third ventricle and lateral ventricles, and metastases in bone, adrenal gland, liver were noted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Lung cancer is a very metastatic cancer, able to spread to the opposite lung, bone, and brain. Therefore, Chen et al also reported the results of a case study of a patient with a brain tumor that had multiple metastases from lung cancer [44]. The patient was treated with standard therapy that had no effects, and metastases transferred from the lungs to the brain, bones, adrenal glands, and liver.…”
Section: Antitumor Effects In Human Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is a very metastatic cancer, able to spread to the opposite lung, bone, and brain. Therefore, Chen et al also reported the results of a case study of a patient with a brain tumor that had multiple metastases from lung cancer [44]. The patient was treated with standard therapy that had no effects, and metastases transferred from the lungs to the brain, bones, adrenal glands, and liver.…”
Section: Antitumor Effects In Human Clinical Trialsmentioning
confidence: 99%
“…After 4 months of monotherapy with H 2 gas (67%) for 2-6 h per day, the size of several brain tumors was significantly reduced, as was the amount of spinal fluid from hydrocephalus associated with the brain tumors. They reported that after one year, all brain tumors had disappeared and the increase in the size of the lung and liver cancers had been controlled [44].…”
Section: Antitumor Effects In Human Clinical Trialsmentioning
confidence: 99%
“…The experimental in vivo studies showed that H 2 inhalation could suppress glioblastoma tumor growth, prolonging the survival of mice with glioblastoma [ 56 ]. In a recent study, data show that, in a patient diagnosed with lung cancer with metastases, H 2 gas monotherapy was associated with a significant effective control of tumors [ 57 ]. The H + -related therapy for the treatment of malignant gliomas is a new therapeutic strategy.…”
Section: Protective Properties Of Molecular Hydrogen: Potential Anmentioning
confidence: 99%
“…These data show that, after standard treatments had failed, hydrogen-gas monotherapy elicited significant effective control of tumors (especially those in the brain), and survival time was lengthened. 8 …”
Section: R Eal W Orld E Vidence Of H Ydrogen O Ncolmentioning
confidence: 99%